Quantifying patient benefit using semi-Markov multi-state models - Jameel, A. Haris (2024)
In the context of oncological drug trials, the semi-parametric Cox proportional hazards model is traditionally used to establish treatment efficacy based on patient response to treatment. However, the analysis is limited to answering questions about treatment efficacy only, since the focus is usually on a single event of interest (such as significant tumour shrinkage).